Clinico-epidemiological profile of eclampsia patients admitted in an urban tertiary care hospital of West Bengal: a record based study - Maji, Baisakhi; Samanta, Sumana; Banerjee, Sreetama; Mullick, Tanjib Hassan; Saharay, Sudhanshu; Sarkar, Debjit (International Journal Of Community Medicine And Public Health, 2018)
Background: Eclampsia is a multi–system disorder with complex pathogenesis, causing 12% of global maternal deaths. It is a major public health problem specially in developing countries, contributing to maternal and perinatal morbidity as well as mortality. Majority of them are preventable if managed timely, promptly and with expertise. The objectives of the study were to identify the incidence of eclampsia in R G Kar Medical College and Hospital as well to identify the determinants of feto-maternal outcome. Methods: A retrospective, record-based cross-sectional study was conducted in an urban tertiary care teaching hospital. There were 354 pregnant women with eclampsia admitted and delivered during the study period which was 1st January-31st December’2015. Complete enumeration was done to get the sample for the study. Data were retrieved from eclampsia registers and log books of delivery kept in the labour room and hospital record section. After wards it was analysed with the help of SPSS 20.0 version to get different inferential statistics. Results: Incidence of eclampsia in that hospital in 2015 was18.4/1000 deliveries. Almost 72% patients had ante-partum eclampsia and rest had post-partum eclampsia. Emergency caesarean section was the most common (62.14%) mode of delivery. Perinatal mortality was found in 5.6% of the eclampsia patients. Majority (65%) of the babies delivered belonged to low birth weight. Muslim patients and the patients of gestational age more than 36 weeks had unfavourable outcome. Conclusions: There is need to educate and encourage the general public for antenatal care and institutional delivery. Along with this the socio-economic, cultural and educational status are to be uplifted for the improvement of the present scenario regarding eclampsia in our country.